TERMINOLOGY AND SPECIALIZED DICTIONARIES: IMPACT AND IMPORTANCE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the significance of terminology and specialized dictionaries in modern linguistics, emphasizing their role in enhancing communication across various scientific and professional fields. It categorizes specialized dictionaries into scientific, technical, medical, and business types while highlighting their importance in ensuring clear communication, meeting professional needs, and facilitating mutual understanding. The contributions of Uzbek scholars, particularly Akmalov and Kurbanov, are discussed in relation to the challenges and advancements in Uzbek lexicography and terminology development. The impact of specialized dictionaries on business, education, and globalization is also examined, underscoring their essential role in fostering effective communication and collaboration. The article concludes by emphasizing the need for continued development and integration of specialized dictionaries with emerging technologies.